2021
DOI: 10.3390/jmse9121442
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Habitat Distribution of Acanthopagrus schlegelii in the Coastal Waters of the Eastern Taiwan Strait Using MAXENT with Fishery and Remote Sensing Data

Abstract: Black sea bream, Acanthopagrus schlegelii, is among the most commercially valuable species in the coastal fishery industry and marine ecosystems. Catch data comprising capture locations for the gillnet fisheries, remotely sensed environmental data (i.e., sea surface temperature, chlorophyll-a concentration, and current velocity), and topography (bathymetry) from 2015 to 2018 were used to construct a spatial habitat distribution of black sea bream. This species is concentrated in coastal waters (<3 nm) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In the autumn, catch rates were predicted to be lower in our investigation, possibly due to the spatial predictions of the GAM models revealing that EKE was the lowest DE. Although, Teng et al [30] mentioned that the movement of the Kuroshio Branch Current in the coastal waters of TS during autumn might substantially impact the habitats of various marine species. However, the catch rates were predicted to be higher and the majority of fishing locations during this period were in the southern part of TS, and relatively higher predictions were in the northeastern part of Taiwan but did not match the observed catch rates (Figure 8d).…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
See 2 more Smart Citations
“…In the autumn, catch rates were predicted to be lower in our investigation, possibly due to the spatial predictions of the GAM models revealing that EKE was the lowest DE. Although, Teng et al [30] mentioned that the movement of the Kuroshio Branch Current in the coastal waters of TS during autumn might substantially impact the habitats of various marine species. However, the catch rates were predicted to be higher and the majority of fishing locations during this period were in the southern part of TS, and relatively higher predictions were in the northeastern part of Taiwan but did not match the observed catch rates (Figure 8d).…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
“…However, the current study had important limitations, such as the SST frontal area, which is associated with the habitat of large pelagic species, and we only use the GLM and GAM models to analyze the spatiotemporal distribution pattern of S. dumerili. Therefore, future research should consider the SST frontal data, and also include other habitat models such as the Geometric Mean Model [7], Arithmetic Mean Model [10], and Maximum Entropy Model [30,76], which one can apply and compare which is better for S. dumerili habitats.…”
Section: Environmental Factors Affecting the Greater Amberjackmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared (IR) imaging technology has been widely used in target search and maritime navigation [1], maritime navigation [2], and maritime environmental variation [3,4]. IR imaging data can reflect object distance information and target shape information within the maritime background in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that hydrodynamic and water quality variables such as water depth, temperature, DO, Chla etc. are important environmental factors affecting the extent of suitable habitats of sh (Zhang et al, 2017;Feng et al, 2021;Teng et al, 2021;Xing et al, 2021). Therefore, understand the relationship between environmental ow regulation and the hydrodynamic and water quality variables is priority.…”
Section: Introductionmentioning
confidence: 99%